Exploring sol–gel zwitterionic fabric phase sorptive extraction sorbent as a new multi-mode platform for the extraction and preconcentration of triazine herbicides from juice samples. (30th March 2022) - Manousi, Natalia; Alampanos, Vasileios; Priovolos, Ioannis; Kabir, Abuzar; Furton, Kenneth G.; Rosenberg, Erwin; Zachariadis, George A.; Samanidou, Victoria F.
Highlights: Preparation of a novel sol–gel zwitterionic multi-mode extraction FPSE medium. Development of a FPSE-HPLC-DAD method for the determination of triazines in juice samples. The zwitterionic sorbent helped cleaning all the acidic interferences from fruit juices. Analysis of commercial and freshly prepared fruit juices. Abstract: Triazine herbicides are a class of common pesticides which are widely used to control the weeds in many agricultural crops. Although many studies have described methodologies for the determination of triazine herbicides in aqueous samples, the attention given to agricultural crops and their products is far more limited. In this study, a novel sol–gel zwitterionic multi-mode fabric phase sorptive extraction (FPSE) platform was developed for the matrix clean-up, extraction and preconcentration of five triazine herbicides from fruit juice samples prior to their determination by high performance liquid chromatography-diode array detection (HPLC-DAD). The novel zwitterionic multi-mode sorbent was characterized and its performance for fruit juice analysis was evaluated. Compared to other sol–gel sorbents, the novel zwitterionic sorbent helped cleaning all the acidic interferences from fruit juices. The herein reported FPSE protocol was optimized and validated. Under optimum conditions, the FPSE method showed good accuracy, precision and sensitivity. The limits of detection and limits of quantification for all analytes were 0.15 ng mL −1 and 0.50 ng mL −1, respectively. The enhancement factors of this method ranged between 36.7 and 51.8. The relative standard deviation for intra-day precision was below 5.6% and for inter-day precision was below 8.8%. Finally, the proposed FPSE-HPLC-DAD method was successfully employed for the analysis of various fruit juice samples.